2022
DOI: 10.1192/j.eurpsy.2022.2335
|View full text |Cite
|
Sign up to set email alerts
|

Early evidence on the mental health of Ukrainian civilian and professional combatants during the Russian invasion

Abstract: Background The ongoing Russian invasion of Ukraine has led many Ukrainians to fight for their country, either in the regular army or as civilian members of voluntary territorial defense forces. There is, however, a dearth of knowledge on the mental health of combatants in this conflict. Prior research on the mental health of combatants is unlikely to translate to the situation at hand because such research is focused on combatants fighting abroad and neglects civilian combatants. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
0
8
1
1
Order By: Relevance
“…The adaption is described elsewhere ( 12 ). In brief, the instrument has five items for emotional (e.g., “I feel helpless,” “I feel frustrated and angry about not being able to do more”) and four items for physical distress (e.g., “I have trouble concentrating,” “I have physical reactions like sweating, shaking, and my heart pounding”) each measured on 5-point Likert scale from not at all (0) to extremely true ( 4 ) scale. The Cronbach alpha for the emotional distress subscale is 0.85 and 0.79 for the physical distress subscale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adaption is described elsewhere ( 12 ). In brief, the instrument has five items for emotional (e.g., “I feel helpless,” “I feel frustrated and angry about not being able to do more”) and four items for physical distress (e.g., “I have trouble concentrating,” “I have physical reactions like sweating, shaking, and my heart pounding”) each measured on 5-point Likert scale from not at all (0) to extremely true ( 4 ) scale. The Cronbach alpha for the emotional distress subscale is 0.85 and 0.79 for the physical distress subscale.…”
Section: Methodsmentioning
confidence: 99%
“…A war has been shown to lead to higher prevalence of anxiety, mood disorders and posttraumatic stress disorder (PTSD) in the general population of the affected country during and for years post-war ( 2 , 3 ). The ongoing war in Ukraine has already been shown to have detrimental impacts on the mental health of Ukrainian military and civilian combatants ( 4 ) and the Ukrainian general population ( 5 ) with nearly half of the participants in both studies displaying clinically relevant symptoms of depression and anxiety. Persons who are internally displaced due to the ongoing conflict between Russia and Ukraine are at an especially high risk for mental health sequelae ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ukrainians, regardless of their professional affiliation, suffer from a sharp change in the usual run of things, situation breakdown, and worsening in all life-activity spheres due to the full-scale war that Russia unleashed on the territory of Ukraine. Any war is always a traumatic and borderline experience because it unexpectedly damages people's life and career plans or prospects and leads to unanswered obstacles and trials (Stone, 2022b;Danylyshyn, 2022) Such a crisis in any person's life causes uncertainty (Pavlova et al, 2022;Suchikova, 2023). People who are constantly under fire are beginning to get used to this new reality, to understand the sounds of incoming shelling, and to look for rules and regularities when they are under fire.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, people exposed to armed conflict on the first front lines of war are at risk of increasing psychological problems [ 8 ]. Pavlova et al [ 9 ] demonstrated that many Ukrainian combatants showed symptoms of anxiety, depression, and insomnia. However, mental health differed depending on closeness to the war area or direct involvement.…”
Section: Introductionmentioning
confidence: 99%